Pola Kehidupan Sosial Ekonomi dan Strategi Bertahan Masyarakat Sekitar Industri Desa Golokan Kecamatan Sidayu - Aulia Sabrina; Martinus Legowo; FX. Sri Sadewo (Universitas Negeri Medan, 2021)
This article or writing aims to determine the pattern of socio-economic life of the community around the industry and to find out the survival strategies of industrialized communities to improve socio-economic life in Golokan village. Technology that is getting more advanced, sophisticated and modern proves that the development is getting faster. Don't care about existence. So that rural areas provide options for distribution. This resulted in a transformation of livelihoods. The transition of the community to their livelihoods from the agricultural sector as farmers and agricultural laborers to the non-agricultural sector as factory workers and opening service businesses. This situation affects various aspects of community life, especially in the socio-economic life that has changed and increased. They can work in the industrial sector as employees and can open businesses. In the past, society had a strong social solidarity. However, without being based on the existence of industry, social solidarity has begun to weaken. The characteristics of rural communities are starting to fade. The more modern society becomes a heterogeneous society, individual, busy working and leaving the social activities that it has been participating in. There is a suitable example in the Sidayu Gresik market area by establishing a family relationship by giving parcels before Eid to each customer, matching the price of goods between one trader and another. Business strategy by behaving well and building social relationships.